Glibenclamide Mimics Metabolic Effects of Metformin in H9c2 Cells - Barbara Salani; Silvia Ravera; Patrizia Fabbi; Silvano Garibaldi; Mario Passalacqua; Claudio Brunelli; Davide Maggi; Renzo Cordera; Pietro Ameri (Cellular Physiology and Biochemistry, 2017)
Background: Sulfonylureas, such as glibenclamide, are antidiabetic drugs that stimulate beta-cell insulin secretion by binding to the sulfonylureas receptors (SURs) of adenosine triphosphate-sensitive potassium channels (KATP). Glibenclamide may be also cardiotoxic, this effect being ascribed to interference with the protective function of cardiac KATP channels for which glibenclamide has high affinity. Prompted by recent evidence that glibenclamide impairs energy metabolism of renal cells, we investigated whether this drug also affects the metabolism of cardiac cells. Methods: The cardiomyoblast cell line H9c2 was treated for 24 h with glibenclamide or metformin, a known inhibitor of the mitochondrial respiratory chain. Cell viability was evaluated by sulforodhamine B assay. ATP and AMP were measured according to the enzyme coupling method and oxygen consumption by using an amperometric electrode, while Fo-F1 ATP synthase activity assay was evaluated by chemiluminescent method. Protein expression was measured by western blot. Results: Glibenclamide deregulated energy balance of H9c2 cardiomyoblasts in a way similar to that of metformin. It inhibited mitochondrial complexes I, II and III with ensuing impairment of oxygen consumption and ATP synthase activity, ATP depletion and increased AMPK phosphorylation. Furthermore, glibenclamide disrupted mitochondrial subcellular organization. The perturbation of mitochondrial energy balance was associated with enhanced anaerobic glycolysis, with increased activity of phosphofructo kinase, pyruvate kinase and lactic dehydrogenase. Interestingly, some additive effects of glibenclamide and metformin were observed. Conclusions: Glibenclamide deeply alters cell metabolism in cardiac cells by impairing mitochondrial organization and function. This may further explain the risk of cardiovascular events associated with the use of this drug, alone or in combination with metformin.